2012
DOI: 10.13085/eijtur.12.1.49-72
|View full text |Cite
|
Sign up to set email alerts
|

Double advantage or disadvantage? – Parental education and children's developmental stages in Italy

Abstract: Thanks for participants of session as well as for Taru Lindblom and for reviewer of eIJTUR for useful comments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Scholars continue to evolve the developmental gradient framework, demonstrating diverse contexts for transmitting intergenerational (dis)advantage by identifying educational differences in developmental gradients. Time-diary studies on Spain, Italy, Germany, and Australia consistently reported a developmental gradient for highly educated parents and more considerable educational differences in children's ages when a given childcare activity is assumed to be critical for child development than other ages (Blaurock & Kluczniok, 2018;Gracia, 2014;O'Flaherty & Baxter, 2020;Rebane, 2015). The developmental gradient framework initially focused on children's academic outcomes and was also adapted to describe parents' health investments.…”
Section: Research Gaps and Study Contributionsmentioning
confidence: 99%
“…Scholars continue to evolve the developmental gradient framework, demonstrating diverse contexts for transmitting intergenerational (dis)advantage by identifying educational differences in developmental gradients. Time-diary studies on Spain, Italy, Germany, and Australia consistently reported a developmental gradient for highly educated parents and more considerable educational differences in children's ages when a given childcare activity is assumed to be critical for child development than other ages (Blaurock & Kluczniok, 2018;Gracia, 2014;O'Flaherty & Baxter, 2020;Rebane, 2015). The developmental gradient framework initially focused on children's academic outcomes and was also adapted to describe parents' health investments.…”
Section: Research Gaps and Study Contributionsmentioning
confidence: 99%
“…This research from the United States shows, for instance, that educated mothers spend more time caring, comforting and playing with their children when they are infants and toddlers, more time in teaching activities (e.g., reading, helping with homework) when children are at school entry, and more time managing, organising and attending outof-home activities during middle childhood and adolescence (Kalil et al, 2012). Evidence for a developmental gradient in educated mothers' time use patterns have been found in Spain (Gracia, 2014) and Italy (Rebane, 2015).…”
Section: Time Spent With Childrenmentioning
confidence: 99%
“…In addition, even lower R 2 values for regression models, ranging from 0.2% to 2.9%, were published by Baxter (2011), Eriksson andOrtega (2011), andMacDonald (2016). Many other research studies on time use published R 2 values of their regression models lower than 10% (Cha, 2021;Gimenez-Nadal, 2010;Khitarishvili & Kim, 2015;Mangiavacchi & Rapallini, 2014;Michelson, 2014;Rebane, 2015). A reason for this could be seen in the fact that people and their responses may not be as predictable and consistent as technical, engineering or computational data.…”
Section: Discussion Of Regression Resultsmentioning
confidence: 99%